2003
DOI: 10.1007/s00253-002-1197-z
|View full text |Cite
|
Sign up to set email alerts
|

Brettanomyces bruxellensis: effect of oxygen on growth and acetic acid production

Abstract: The influence of the oxygen supply on the growth, acetic acid and ethanol production by Brettanomyces bruxellensis in a glucose medium was investigated with different air flow rates in the range 0-300 l h(-1 ) x (0-0.5 vvm). This study shows that growth of this yeast is stimulated by moderate aeration. The optimal oxygen supply for cellular synthesis was an oxygen transfer rate (OTR) of 43 mg O(2) l(-1) x h(-1). In this case, there was an air flow rate of 60 l h(-1) (0.1 vvm). Above this value, the maximum bio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
34
0
4

Year Published

2007
2007
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(41 citation statements)
references
References 11 publications
3
34
0
4
Order By: Relevance
“…This yeast has low nutritional requirements [8], and is well known to be sensitive to oxygen availability [9,10]. Custer (1940) (cited in [4]) found that resting cells of Brettanomyces claussenii under aerobic conditions fermented glucose at a higher rate than in the absence of oxygen.…”
Section: Introductionmentioning
confidence: 99%
“…This yeast has low nutritional requirements [8], and is well known to be sensitive to oxygen availability [9,10]. Custer (1940) (cited in [4]) found that resting cells of Brettanomyces claussenii under aerobic conditions fermented glucose at a higher rate than in the absence of oxygen.…”
Section: Introductionmentioning
confidence: 99%
“…On the contrary, when some non-conventional yeasts are employed (i.e., Torulaspora delbrueckii and Brettanomyces spp. ), low level of oxygen is necessary to support fermentation [26,27]. In the case of co-cultivation of Saccharomyces and nonconventional yeasts, this dependence on oxygen may play a positive role in controlling the growth of the latter, thereby ensuring successful completion of fermentation by the former.…”
Section: Non-conventional Yeastsmentioning
confidence: 99%
“…These yeasts spoil beer through the production of the highly volatile phenolic compounds 4-ethylguaiacol and 4-ethylphenol, lending the aroma of bandages, sweat, and smoke. A number of other metabolites, including copious acetate production in the presence of oxygen (234), result in a wide range of off-flavors produced by these yeasts. In spite of its reputation, Brettanomyces is a desired component of certain beers, particularly Belgian lambic (see below) and fruit beers, in which its beta-glycosidase activity enhances fruit aroma (235).…”
Section: Pediococcus Damnosus Pediococcus Inopinatus Pediococcus Dementioning
confidence: 99%